The quest for moral leaders essays on leadership ethics - Ciulla, Joanne B.; Price, Terry L. 1966-; Murphy, Susan E. (New horizons in leadership studies, 2005)
In The Quest for Moral Leaders, the contributors explore how leaders themselves view their role, as well as the ways in which leadership functions within business, politics and society. The volume begins with chapters examining how religious beliefs and emotions color the way leaders make decisions. The second section covers how leaders think about morality, while the book's final chapters shift our attention to the function of leadership within organizations." "The first book to offer perspectives on leadership ethics from ancient Greek ideas on reverence to the moral problems of executive compensation, The Quest for Moral Leasers is a must-read for scholars and students of leadership, ethics and business. Leadership consultants will also find this in-depth analysis a valuable resource.